Diversity and dynamics of microbial population during fermentation of gray sufu and their correlation with quality characteristics. (15th April 2023) - Ding, Siqi; Tian, Meng; Yang, Liu; Pan, Yue; Suo, Linglan; Zhu, Xianming; Ren, Dayong; Yu, Hansong
Abstract: The quality of gray sufu has been significantly influenced by microbes, but little is known about the spatiotemporal changes in microbes during fermentation and how they relate to quality. This study showed that after 28 days of fermentation, the texture and physicochemical indexes of gray sufu reached the best, and the taste was better on the 21st day. On the surface of gray sufu, the abundance of Bacillus and Trichosporon increased over time, while Lactobacillus, Pediococcus, and Pseudomonas decreased. In the middle and central parts, the abundance of Lactobacillus and Sarocladium increased over time, while Pediococcus, Pseudomonas, and Apiotrichum decreased. Physicochemical index (pH, amino acid nitrogen, TCA-soluble peptide), biogenic amines and benzoic acid were negatively correlated with the genera Pediococcus, Pseudomonas and Apiotrichum, while positively correlated with Sarocladium and Trichosporon . Propionic acid was positively correlated with Pediococcus and Pseudomonas but negatively with Apiotrichum . This demonstrated that the microflora in gray sufu has a spatiotemporal distribution and is associated with the product quality. Tracker analysis demonstrated that yellow serofluids, salt brine, and tofu pehtze provided microflora for fermentation. This study would be useful in understanding the production mechanism of gray sufu and strengthening its quality control by developing microbial regulation strategies. Graphical abstract: Image 1 Highlights: The microorganisms in gray sufu showed spatial and temporal distribution. The values of all safety indices were below the limit. The microorganisms of gray sufu were mainly originate from the three raw materials. The dominant microorganisms were closely related to the quality characteristics.